(untitled) (Journal of Health Sciences, 2017)
Introduction: Family is a strong communicative base of adolescent development, even though environment has its own influence as well. The study links the risks and substance use (tobacco, alcohol, and drugs) among adolescents to their perception about the functioning of family. Hence, a model of functional communication has been established aimed at preventing the defined problem. Methods: A random, voluntary, and anonymous survey was conducted that included a non-clinical sample of 1.018 adolescents in the Tuzla Canton. In a prospective method, the Youth Risk Behavior Surveillance System of the World Health Organization (WHO) was used, modified for this study. Results: The average prevalence of substance use is 81.2% and is significant for male adolescents. Some 33% of the respondents smoke tobacco, 25.4% drinks alcohol, while 12% of the surveyed adolescents use drugs. There is a significant correlation between a complete and broader family and tobacco and alcohol use, while incomplete family and household without family members are linked to tobacco use only. The risk of alcohol use is significantly related to father’s higher level of education while mother’s high school education is significantly related to tobacco and alcohol use. As perceived by adolescents, parents have negative attitudes about substance use (75%), they are more strict in setting the rules of behavior at home (45.5%) than outside, and control where more than with whom adolescents spend their free time (F=14.14, df [2.6], p<0.05). Conclusion: The functioning of a family (family structure, parents’ education, and the quality of communication in a family) is a significant factor in the context of tobacco, alcohol, and drug use.